2015
DOI: 10.2340/00015555-1896
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous Tone in Vitiligo Patients – A Case-control Study

Abstract: In this cross-sectional, exploratory case-control study the vegetative arousal in vitiligo patients compared to an age and gender matched healthy control group was assessed. Forty-eight participants (24 outpatients with generalised vitiligo and 24 healthy controls) completed a test procedure consisting of an initial period of rest (R1), a defined mental stress task (the d2 test of attention), a second period of rest (R2) followed by an individually, age adapted physical stress task (bicycle ergometry) and a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This case series showed that prolonged periods of psychological stress might be involved in the onset and progression of the vitiligo. These associations may support the view that psychological stress and the onset of autoimmune conditions are closely connected [ 17 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This case series showed that prolonged periods of psychological stress might be involved in the onset and progression of the vitiligo. These associations may support the view that psychological stress and the onset of autoimmune conditions are closely connected [ 17 ].…”
Section: Discussionsupporting
confidence: 72%
“…However, no therapeutic study has yet shown long-term benefits using these criteria, and further research is required to establish evidence for the effective treatment of vitiligo [ 1 , 12 14 ]. There has been at least one prospective observational clinical study that has investigated the effectiveness of classical homeopathic treatment of vitiligo [ 15 ], with a further prospective observational clinical study involving homeopathic treatments given based on characteristic individualized patient symptoms [ 16 , 17 ]. However, to our knowledge, we now report the first retrospective case series describing the long-term effects of the homeopathic treatment of vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of our systematic review, conducted according to the PRISMA guidelines, was to assess the differences among genders in HRQoL and in psychologic symptoms among persons with vitiligo. The qualitative assessment of the 12 eligible studies (Kent and Al'Abadie, 1996;Ongenae et al, 2005;Al Robaee, 2007;Schmid-Ott et al, 2007;Sampogna et al, 2008;Ingordo et al, 2014;Krüger and Schallreuter, 2015;Trapp et al, 2015;Dabas et al, 2020;Abdullahi et al, 2021;Do Bú et al, 2022;Ning et al, 2022) revealed a wide heterogeneity in term of methodology, as well as in terms of quality among studies. The design of all the studies included in the review was cross-sectional.…”
Section: Discussionmentioning
confidence: 99%
“…All collected records are cross-sectional, observational studies, except for Trapp et al (2015) that is described as age and gender matched "exploratory case control study, " respectively. The total sample collected in this review includes 2,264 participants with vitiligo; 91 with Acquired Dermatological Macular Hyperpigmentation; 86 with Melasma; 128 with Psoriasis; and 99 were healthy controls.…”
Section: Features Of Included Findingsmentioning
confidence: 99%